Moving out of poverty: rising from the ashes of conflict (Vol.4) - Narayan, Deepa (ed.); Petesch, Patti (ed.) (New Delhi, 2012)
This volume brings together findings and lessons about why and how people move in and out of poverty in conflict-affected contexts. It features cross-country findings on conflict and mobility, as well as in-depth case studies of six countires affected by signigicant violent conflict during the ten-year period covered by the research.
Keywords: Poverty